The Representation of Samuel Huntington's Clash of Civilization in Buried - Guruh Putra Tama (English Research Journal : Journal of Education, Language, Literature, Arts and Culture, 2018)
This research focuses on civilization clash taking place in Baqubah, Iraq during War on Terror campaign portrayed by Buried, a film released in 2010. It is conducted under American Transnational Studies frame, and uses socio-cultural and historical approach to construct the thesis. It considers research from Rwaida Gharib (2009) and Jasna Poljak Rehlicki (2015) as the foundation to continue the discussion of civilization clash in Baqubah, Iraq. It employs Samuel Huntington’s Clash of Civilization theory to determine factors causing civilization clash to occur. Its objective is to describe the representation of Samuel Huntington’s Clash of Civilization in Buried. This research discovers that Buried depicts Samuel Huntington’s Clash of Civilization: difference among civilization, interaction among civilization, economic modernization, the growth of civilization-consciousness, and complexity of cultural characteristics and differences.   Keywords:  clash of civilization, war on terror, American transnational studies